Measuring urban precariousness and its relation to disaster risk management - Juliette Marin; Ingrid Mendez; Juan Pablo Sarmiento (Revista de Estudios Latinoamericanos sobre Reducción del Riesgo de Desastres, 2018)
Urban processes, characterized at the global level by their acceleration and informality, and the increase of people living in areas prone to hazards, present a major social issue that requires a re-reading of urban precariousness from a risk reduction perspective. By analyzing 23 urban settlement precariousness indicators, this article seeks to characterize the multicausality, multidimensionality and to identify trends in the use of precariousness models. Through the consideration of physical, socio-economic, socio-political and legal dimensions of urban precariousness, and the analysis of their connections with risk factors, we intend to deepen the understanding of the interrelation of these concepts. It is shown that, although these dimensions are not always directly related to risk factors, their links can potentiate the generation of risk that in turn can accentuate precarious conditions, so they should not be analyzed separately. Finally, the study contributes in the formulation of a tool for characterizing urban precariousness, for decision making and the development of territorial intervention plans, which directly integrate risk while representing more appropriately the multidimensionality of precariousness.